A Meta-Analysis Linking Parent-to-Child Aggression and Dating Abuse During Adolescence and Young Adulthood. (December 2021) - Goncy, Elizabeth A.; Basting, Evan J.; Dunn, Courtney B.
Relationship continuity and social learning theories provide support for parent-to-child aggression as one potential explanatory factor for dating abuse (DA); however, empirical results are mixed across studies as to the strength of this association. This meta-analysis sought to estimate the overall size of this effect among adolescent and young adult samples and investigate potential moderating factors including sample and measurement variables. Records were identified using a computerized search of databases with several keywords. Peer-reviewed journal articles and dissertations were included if they measured both parent-to-child aggression and DA perpetration and/or victimization among adolescents (aged 12–18) or young adults (aged 18–29). Sixty-six records met inclusion criteria, yielding 370 unique effect sizes for the relation between parent-to-child aggression and DA across 94 unique samples. As hypothesized, there was a small-to-medium effect size between parent-to-child aggression and subsequent DA during both adolescence and young adulthood. The strength of these findings was consistent across DA outcome (perpetration and victimization) and both physical and psychological forms, youth and parent gender, and youth age. Stronger associations were found when the gender of the parental aggressor was undefined compared to either a defined paternal or maternal aggressor. Records using the Conflict Tactics Scale to measure both parent-to-child aggression and DA yielded stronger associations compared to sources that used different measures, but single informant versus multiple informants did not yield any differences.